Game Simulasi Pemilihan Calon Presiden Menggunakan Metode Finger Detection - Anang Habibi; Sitti Khairunnisak; Dipa Pradewa Alfiansyah (STIKes Ibnu Sina Ajibarang, 2024)
The presidential election simulation game using the Python programming language is designed to provide players with an interactive experience in protecting society through the leadership election process. In this game, players will choose between several presidential candidates represented by a specific character. Each nominee has a different platform and vision, and players must make smart decisions to meet the needs and expectations of society. Through a game mechanism that involves policy choices, campaigns, and community responses, players will experience the impact of political decisions on community conditions in a simulated manner. The player's score or achievement will be reflected in the level of public support obtained by the selected candidate. The ultimate goal is to provide players with an understanding of the complexities and responsibilities of choosing leaders who are able to protect society well.